Medical antiques - About Cucumber or "Mata Serrano" - Ache, Doctor (1922)
Twenty years ago about was not even debatable, in the field of Popular Medicine, the harmful effects exerted on the human body by eating unripe fruits; dysentery was attributed to the ingestion of these fruits, some of which, such as plum, for example, were considered disenterígenos yet to ripeness.